2019
DOI: 10.1093/aob/mcz184
|View full text |Cite
|
Sign up to set email alerts
|

Stress signalling dynamics of the mitochondrial electron transport chain and oxidative phosphorylation system in higher plants

Abstract: Background Mitochondria play a diversity of physiological and metabolic roles under conditions of abiotic or biotic stress. They may be directly subjected to physico-chemical constraints, and they are also involved in integrative responses to environmental stresses through their central position in cell nutrition, respiration, energy balance and biosyntheses. In plant cells, mitochondria present various biochemical peculiarities, such as cyanide-insensitive alternative respiration, and, besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 192 publications
0
29
0
Order By: Relevance
“…In this study, mitochondria were seen deformed both in terminal and median leaves, and primary and secondary roots of upland cotton under Pb exposure. These changes may be attributed to excess ROS generation, as mitochondria release free electrons in electron transport chain to form O •− and other ROSs (Dourmap et al, 2019). As a first line defense, SODs neutralize O •− in mitochondria, that's why SOD activity was increased in GSH + Pb group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mitochondria were seen deformed both in terminal and median leaves, and primary and secondary roots of upland cotton under Pb exposure. These changes may be attributed to excess ROS generation, as mitochondria release free electrons in electron transport chain to form O •− and other ROSs (Dourmap et al, 2019). As a first line defense, SODs neutralize O •− in mitochondria, that's why SOD activity was increased in GSH + Pb group.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme levels of abiotic stresses such as drought, flooding, salinity, mineral deficiency, low or high temperatures, high light, post-harvest problems, and accumulation of reducing sugars during cold storage have negative impact in crop yield ( Le Gall et al, 2015 ). Abiotic stresses usually lead to superoxide overproduction in mitochondria ( Dourmap et al, 2019 ). The mitochondrial respiratory chain in higher plants consists of the ATP-coupling cytochrome pathway (CP) and the cyanide (CN)-resistant respiratory pathway.…”
Section: Potato and Application Of Crispr/cas Systemmentioning
confidence: 99%
“…A recent study has also demonstrated that chloroplast-localized SDP, which affects rRNA processing in chloroplasts under normal conditions, has positive effects on salt, heat, freezing, or UV stress tolerance, as it influences the stress-responsive genes in the nucleus [ 117 ]. Beyond organelles, it will be of great interest to investigate how nCMRBP-mediated organellar retrograde signaling (ORS) influences the reprogramming of the expression of stress-responsive nuclear genes, and the organellar and nuclear epigenetic modifications for stress priming and memory [ 101 , 118 , 119 , 120 , 121 ]. Although the study of organellar proteomics and metabolomics is far behind than those in the nucleus and cytoplasm, recent studies emphasize the importance of homeostasis between the nucleus and organelles in plant acclimation to environmental changes [ 122 , 123 , 124 , 125 ].…”
Section: Physiological Functions Of Ncmrbps In Abiotic Stress Respmentioning
confidence: 99%